Stockhausen 33: Aries - Klavierstuck XIII - Stockhausen, Markus; Stockhausen, Majella; Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1994)
ARIES for trumpet and electronic music (Markus Stockhausen)PIANO PIECE XIII (LUCIFER'S DREAM as piano solo) (Majella Stockhausen).......